CRITICAL DISCOURSE ANALYSIS: REVEALING MASCULINITY THROUGH L-MEN ADVERTISEMENT - Janata Shoji Al Falaq; Dian Puspita (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
in this article, the writers aim to look deeper into the ideology used by L-men advertising management in making L-men advertisement which mostly used male casting and other topless act. Using critical discourse analysis, the article focus on the implicit messages convey by the L-men advertisement that it conveys about the toxic masculinity behavior in gaining men dominance is equal to have a strong and muscular body. This study uses the Fairclough model of analysis, that in the shown that the creator of the advertisement-supported the current represe about gaining muscle to gain dominance, and the society ignorance towards the issue and only look advertisement as it sells product only.